(untitled) (UKLO Proceedings, 2025)
Multidisciplinary approach is essential for the study of literature, and many modern literary theoretical concepts include multi-aspect analysis and tools from various scientific fields (psychology, linguistics, and even mathematics). All theories about the emergence of the female script, feminism and gynocriticism are directly related to the fifth sustainable development goal of the UN on gender equality - to achieve gender equality and emancipation of women and girls.To consider the female character in the literary texts, according to the already known and elaborated application theories is not only a challenge, but also an opportunity for a better and different interpretation of the text, which through such an analysis facilitates communication with the recipient. It also gives a new meaning to literary texts, to the characters in them and expands the mysterious stories to the level of educational, instructive content.Feminism in the modern and postmodern reveals new space for building new point of views and judgments about the characters. In„Dialectics of the Enlightenment“ (Horkheimer and: 2002) state that women are equated with nature and men with culture. Max Horkheimer and Theodor Adornoshow a scheme in which the woman is interpreted as nature - an object, and the man as a culture - subject and confirmation of the perception that modern men have about women. As I mentioned above, Horkheimer and Adorno and twentieth-century gender studies found modern culture in gender binarism. Dubravka Oraic - Tolic lists key gender oppositions.Precisely the analysis of the characters (Mara in "Mara’s Wedding" by Vladimir Kostov and Velika from "Pyreus" - PMA) according to the key gender oppositions, confirm that in Macedonian literature, at least in the indicated examples, there is no doubt about misogyny, but on the contrary, adoration of feminine power. Hence, isn’t it the greatest contribution to raising awareness of gender equality and a different perception of women?